PENINGKATAN PERFORMA REPRODUKSI IKAN PATIN SIAM (Pangasianodon hypophthalmus) PADA MUSIM KEMARAU MELALUI INDUKSI HORMONAL [Reproduction Improvement on Female Striped Catfish Pangasianodon hypophthalmus at Dry Season By Hormonal Induction] - Tahapari, Evi; Dewi, Raden Roro Sri Pudji Sinarni (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Striped catfish (Pangasianodon hypophthalmus) spawning success is strongly influenced by environment.Striped catfish spawning generally occurs during the rainy season while in the dry season is difficult to find mature female. This research was conducted to improve reproduction performance of female striped catfish during dry season through combination injection of hormone pregnant mare serum gonadotrophin (PMSG) and human chorionic gonadotrophin (HCG).The treatments were A : control (no hormone injections), B : injection of PMSG 10 IU/kg + HCG 10 IU/kg and C : injection of PMSG 20 IU/kg + HCG 10 IU/kg.Injections were done at interval of two weeks as many as six times. The research was conducted during dry season in June-October 2012 with rainfall 0.20- 14.40 mm/years. The results showed combination injection of PMSG + HCG could improve female reproduction performance. The best treatment was shown on C treatment with values of OSI (ovi somatic index), fecundity, fertilization rate, hatching rate and larva production was 12.18 %, 523 000 eggs/female, 79.65 %, 69.93 % and 290 000 larvae/female respectively. As for control treatment (A) the value of OSI, fecundity, fertilization rate, hatching rate and larval production, was 6.45 %, 197 000 eggs/female, 48.55 %, 35.59 % and 34 000 larvae/female, respectively